2019
DOI: 10.1097/olq.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cannabis Use, Sexual Behavior, and Sexually Transmitted Infections/Human Immunodeficiency Virus in a Cohort of Young Men Who Have Sex With Men

Abstract: In a longitudinal Los Angeles study of men who have sex with men there were fewer sexually transmitted infections when men reported exclusive cannabis use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…SMY are at an increased risk of cannabis use [21,22,23]. A systematic review of Canadian studies revealed that cannabis use is consistently higher in SMY than in heterosexual respondents, with sexual minority young men and bisexual youth having greater risk than young women or those identifying as lesbian or gay [24].…”
Section: Introductionmentioning
confidence: 99%
“…SMY are at an increased risk of cannabis use [21,22,23]. A systematic review of Canadian studies revealed that cannabis use is consistently higher in SMY than in heterosexual respondents, with sexual minority young men and bisexual youth having greater risk than young women or those identifying as lesbian or gay [24].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency of cannabis use did not change CS risk. While a similar lack of effect on CS and STI outcomes has been apparent in studies of adolescents, young adults, and MSM [42,[47][48][49][50][51][52],, other studies have found the opposite [27][28][29][30]. Several wide-ranging factors may be driving differences in findings; these include population-level factors (e.g., age, gender, sexual orientation); social factors (e.g., relationship type and duration, power dynamics surrounding sexual behavior, and the role of intentionality to use condoms in the context of cannabis use); factors specific to cannabis and its use itself (e.g., drug potency, dependency, tolerance to its effects); study design factors, such as social desirability bias from particular data collection methods.…”
Section: Discussionmentioning
confidence: 66%
“…Due to possible anti-inflammatory effects, cannabis use may also lower the odds of neurocognitive impairment in people with HIV infection [50]. Regarding the impact of cannabis on sexually transmitted infections (STIs), the data show that there were fewer STIs and lower risk of sexual engagement among HIV-infected MSMs who smoked cannabis as compared to those who did not smoke cannabis [72]. On the positive side of cannabis use, research shows that cannabis improves appetite, food intake, and metabolism, possibly via the endocannabinoid system, which, in turn, activates appetite stimulating hormones such as ghrelin and leptin [40,41].…”
Section: Discussionmentioning
confidence: 99%